Partisipasi Masyarakat dalam Pengelolaan Hutan di Kelurahan Tabona Kota Ternate - Sabaruddin B; Much Hidayah Marasabessy; Rudi Mansyur; Khaerum Nisa; Sadam S Husein; Anugrahandini Nasir (Universitas Khairun, 2026)
Community access to forest management within protected areas has been strengthened by the enactment of a policy known as social forestry. Data indicates that the achievements of the social forestry program through 2025 amount to 8.3 million hectares, or approximately 54% of the national target of 15.3 million hectares. However, behind these program achievements, there remain a number of challenges on the ground, such as limited capacity among beneficiary groups, bureaucratic obstacles, and insufficient post-approval support. The objective of this study is to determine the level of understanding, participation, as well as institutional arrangements and support following the designation of social forestry areas in the Tabona urban village. This study employed a mixed-methods approach, combining qualitative and quantitative descriptive methods, with research subjects selected using provocative sampling. Data analysis involved data collection, data condensation, data presentation, and drawing conclusions and verification. The results of the study indicate that the community’s level of knowledge regarding the social forestry program is relatively good, ranging from 73.3% to 93.3% across all measured indicators. Community participation showed fairly good results, with the percentage of involvement in some indicators exceeding 73%. The community’s overall perception of the benefits of the social forestry program fell into the “agree” category, with an average score of 34.2%. Institutional strength indicated a robust traditional-based internal system at 73.3%. Keywords: Social forestry, Participation, Perceptions, Tabona Village Institutions